ICT for young indigenous people: Creating collective digital cultural contents a Mapuche experience (Quinto Sol, 2013)
In this paper we analyze “Information and Communication Technologies for Young Mapuche People” and the context in which they emerged, related with the International Summits on the Society of Information and how it relates with ethnic identity construction processes. We discuss the concept of cultural authenticity, the new relationship between indigenous peoples and the academic world, and the anthropologist's role in applied social projects.
Keywords: Indigenous peoples; ICT; ethnic identity; authenticity; anthropologist's role